Banco Central e os sentidos sociais da ação em política monetária : as justificações morais distintas dos usos sociais do dinheiro - Silva, Márcio Rogério (2017)
It is a study about the social meanings emerging from the monetary policy action of the Central Bank of Brazil (BCB) between 1995 and 2016, using comparisons with agents of the Federal Reserve (Fed), European Central Bank ( ECB) and pressure groups inserted in a broader social space, aiming to understand the social meanings of decision making on such a policy, based on structural and moral inheritances throughout the historical process of the role of the Central Banks. Under the sociology of Boltanski and Thevenot's critical capacity, supported by the prosopography, narrative, content, and financial statements methods, by reference to situational disputes over interest rates, it was possible to demonstrate that there are moments in which there is convergence between the position and the Position at the BCB, while at other times they influence more public-economic-financial coalitions or the performative pressure of groups outside of power, especially in cultural disputes that open up larger areas of opposition, opposing Hawkish practices to practices Dovish (monetary easing), emerging moral senses of accusation and defense. Finally, it was concluded that the monetary counter-performance between 2011 and 2014, contrary to the equivalence agreements in monetary policy, was one of the important variables for the establishment of a political crisis, along with other multisectorial factors. To this end, this tension has indicated a meta-heuristic operator of interest and debt which anchors high interest in technical-moral justifications, as justification in the "sacrifice" and "just reward" to financiers and as "punishment" to the "irresponsible".